Analysis of the Application of Article 18 of the Consumer Protection Law in Tourism Services - Chusnida, Nabilah; Widyanti, Yenny Eta; Djumikasih, Djumikasih (IJBLE Scientific Publications Community Inc., 2024)
The focus of this research is to reveal the extent to which the provisions of Article 18 UUPK have been implemented by tourism businesses to protect consumer rights and security. The research method uses an empirical sociological approach which uses field data as the main data source, such as the results of interviews, observations and documentation. The results provide a comprehensive picture of the practice of implementing Article 18 UUPK in the tourism services sector. These findings involve evaluating the transparency of information, security, and quality of services provided to consumers. That the main obstacles and challenges lie in human resources, and the factor of lack of awareness on the part of tourism actors. It is hoped that this in-depth study can contribute to improving policies and implementation of Article 18 UUPK, as well as increasing consumer protection in the context of tourism services.